Analisis Strategi Survival Pada Bisnis Travel Haji dan Umrah Saat Pandemi Covid-19 Di Shafira Tour & Travel - Azrul Afrillana Awaludin; Ahmad Khairul Hakim (Journal of Islamic Management, 2023)
This research aims to analyze the survival strategy of Shafira Tour & Travel during the Covid-19 pandemic and the factors that hinder the process of implementing a survival strategy. Metode qualitative research case studies with exploratory types of research. The data collection techniques used are in-depth interviews, participant observations, and documentation. The data validity technique used is the triangulation of data sources and techniques. The result of this research is that the survival strategy implemented by Shafira Tour & Travel is the result of integrating the company's three functions: operational management, marketing and finance. Meanwhile, the factors that hinder the implementation of survival strategies consist of internal and external factors